Wybrane kierunki i przesłanki tworzenia sieci logistycznych - Brdulak, Halina (Selected Directions and Sourles of the Logistics Networks Creation, 2005)
In the study there were pointed out main, in the authoress' opinion, factors, which have a great impact on the development of the net organizations including logistics network organizations and also were defined the possible strategies of theirs' acting due to the EU accession. From the authoress' point of view, the relations based on the trust are becoming a principle of acting of all net organizations. Preceding issues can be found mainly in the theory of localization, resource theory and key competences on the one hand, and on the other hand - theory of transaction costs, agency and network theorie. The crucial factors, which coduce a new view on the strategies are: globalization, cost and time pressure, moving the last stage of production to the consumer's side, outsorcing and offshoring as well as the industrialization of services. In this study, as an example were given the changes in location of European Distribution Centers resulted from the UE enlargement and the principles of building up Polish System of Distribution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 27-35